AVALIAÇÃO DO DESEMPENHO EMPRESARIAL APLICADA À MANUTENÇÃO:UMA ABORDAGEM SISTÊMICA - Carvalho, Nelson Cabral de (2005)
This study regards the management and the factors that influence the organizational improvement Culture, Strategy, Organizational Structure, Management Model, Performance Evaluation, and Excellence References, with focus in the Business Performance Evaluation as a success critical factor in the Organizations management. The success is not a fortuity event, being actually the product of a construction process, initiated with a perception of the environment where it operates and shall participate, harmonically and constructively, in order to reach its objectives and goals, and performing its Mission and Vision. Therefore shall consider and take into account, as well as adjust its own culture, according to the present paradigm or being the rulers of the environment where it operates. Disregarding this concept and not promoting the necessary adjusts, the strategic plan and all the other aspects of the process may become ineffective and ordinary burocratic documents. Then, Organizational Culture is the one that will influence the Business Strategy that will guide the definition of the Organizational Structure. Management Model elaborated to make the Organization work effectively to support the defined strategy will condition the Organization Performance and shall content an evaluation system that will provide self-knowledge and the guides to adjust management actions. Among the systems and instruments used for performance evaluation and strategic monitoring available on literature and consulting business, are analyzed only the most usual, regarding the proposed goals of the function. The use of these instruments of performance evaluation is discussed related to its adjustment to an Organization as a whole and its parts. Among these parts or subsystems of the Organization is the Maintenance, that is analyzed in terms of its strategic impact in the Organization results and business. Due to this importance and impact, and taking in account that performance evaluation is fundamental for the Organization success, a proposal of performance evaluation models to be applied to maintenance is placed, as well as their characteristics and appliance strategies.